2014
DOI: 10.1111/bjd.12989
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated regulation of melanoma

Abstract: Melanoma is one of the most aggressive and deadly skin cancers, and, in its advanced stages, accounts for > 80% mortality. The incidence of melanoma is increasing worldwide; however, beyond surgical removal of the tumour, there is currently no curative therapy available, especially for its advanced stages. This may, in part, be owing to incomplete understanding of the molecular mechanisms that regulate the initiation and/or progression of melanoma to metastasis. The molecular mechanisms leading to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 74 publications
(236 reference statements)
0
21
0
1
Order By: Relevance
“…MiRNAs trigger mRNA degradation, stability or inhibition of translation by binding to specific target mRNA [32]. Accumulating evidence has suggested that dysregulation of miRNAs exerts an important role in MM progression by functioning as oncogenes or tumor suppressors [33]. Although many dysregulated miRNAs have been identified in MM, it is believed that there are still a large number of miRNAs uncovered and their unknown roles in MM progression need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs trigger mRNA degradation, stability or inhibition of translation by binding to specific target mRNA [32]. Accumulating evidence has suggested that dysregulation of miRNAs exerts an important role in MM progression by functioning as oncogenes or tumor suppressors [33]. Although many dysregulated miRNAs have been identified in MM, it is believed that there are still a large number of miRNAs uncovered and their unknown roles in MM progression need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is emerging that also microRNA (miRNA) play an important role in melanoma biology acting as tumor suppressors or oncogenes [5,13,14]. Among these, miR-211 is almost restricted to the melanocyte lineage and is reported as the miRNA most differentially expressed between normal melanocytes and non-pigmented melanoma cell lines and primary melanomas from patients [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, c-kit modulates microphthalmia-associated transcription factor (MITF) and tyrosinase, which are mutated in melanoma cells. Depending on the cell stage of melanoma, it seems that miR-221 and miR-222 can have various targets (Table 1) (16)(17)(18)(19)(20).…”
Section: Cell-cycle Regulatory Overexpressed Mirnasmentioning
confidence: 99%
“…Considerably, these miRNAs perform their roles by reducing eukaryotic translation initiation factor (eIF4E) in melanoma cell lines (Table 1). MiR-145 is another moderator of cell cycle with different functions (1,20,43,44). MiR-145 inhibits cell reproduction owing to the adherence of c-myc and Erbb3; this function is prevented due to miR-145 depletion (38)(39)(40).…”
Section: Cell-cycle Regulatory Downregulated Mirnasmentioning
confidence: 99%
See 1 more Smart Citation